2003
DOI: 10.1080/01650250344000046
|View full text |Cite
|
Sign up to set email alerts
|

Compliance in Chinese and Canadian toddlers: A cross-cultural study

Abstract: Observational data concerning children’s compliance were collected from samples of 2-year-olds in PR China and Canada. Information on child-rearing attitudes was obtained from mothers. It was found that Chinese toddlers had higher scores on voluntary committed compliance than their Canadian counterparts. In contrast, Canadian toddlers had higher scores on externally imposed or situational compliance and overt protest than Chinese toddlers. Girls displayed more committed compliance than boys in both samples. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 53 publications
5
106
0
3
Order By: Relevance
“…Thus, from a young age Chinese children are taught to suppress impulsivity, anger, and aggression (Cheah and Rubin 2004;Wang et al 2006). Conversely, cultural values concerning the importance of effortful behavior underpin Chinese parents' socialization practices around rigorous, early self-control training (Chao et al 2000;Chen et al 2003). Practices described above predict differences in children's behavior across different cultural contexts.…”
Section: Early Socialization Experiencesmentioning
confidence: 94%
“…Thus, from a young age Chinese children are taught to suppress impulsivity, anger, and aggression (Cheah and Rubin 2004;Wang et al 2006). Conversely, cultural values concerning the importance of effortful behavior underpin Chinese parents' socialization practices around rigorous, early self-control training (Chao et al 2000;Chen et al 2003). Practices described above predict differences in children's behavior across different cultural contexts.…”
Section: Early Socialization Experiencesmentioning
confidence: 94%
“…For example, Nelson et al (2006) suggested that Chinese parents are more directive in their strategies to encourage their children to fi t in with their peers and help their children learn socially acceptable behavior. Chinese mothers have also been found to be more accepting of their children ' s inhibited behavior than North American mothers (Chen et al, 1998 ). Yet, in more recent work, social withdrawal was reported to be negatively valued by Chinese mothers of preschool children (Cheah & Rubin, 2004 ).…”
Section: Parentingmentioning
confidence: 99%
“…For example, reserved, inhibited behavior (Chen et al, 1998 ) may be interpreted as refl ecting a cooperative, compliant demeanor, and thus may be viewed as acceptable behavior. Nonsocial and withdrawn behavior in social company (Cheah & Rubin, 2004 ) may be viewed as an uncooperative, unacceptable form of behavior.…”
Section: Parentingmentioning
confidence: 99%
“…learning styles (e.g., Geary et al 1996) to such social-personality concepts as conformity (e.g., Kim and Markus 1999) and compliance (e.g., Chen et al 2003). Different theories focusing on different facets of the multidimensional concept of culture have been proposed to provide primarily proximate explanations of the observed East-West differences.…”
mentioning
confidence: 99%